2021
DOI: 10.1021/jacs.1c02133
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Induced Cross-Linking of Polymers via C,H Insertion Cross-Linking (CHic) under Mild Conditions

Abstract: The focus of studies performed so far on the formation of surface-attached polymer networks by C,H insertion cross-linking (CHic) reaction has been largely on photochemical activation. This study describes the thermal activation of the formation of (surface-attached) polymer networks under comparably mild conditions. A novel cross-linker, based on a diazo phenyl ester group, is incorporated into various copolymers, which are subsequently deposited on solid substrates. Upon activation, the cross-linker moieties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…31−33 A macromolecular cross-linker containing the diazo groups was elegantly reported and applied in the surface modification. 34,35 Herein, we report that the cross-linker containing a multidiazo moiety can be synthesized from commercial diols and triols using esterification and the Regitz diazo transfer reaction (Scheme 1C). The thermal decomposition of the synthesized first and second generations of cross-linker 1G and 2G provides the corresponding bis-carbene that cross-links the linear polymer chains by C−H activation and insertion.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31−33 A macromolecular cross-linker containing the diazo groups was elegantly reported and applied in the surface modification. 34,35 Herein, we report that the cross-linker containing a multidiazo moiety can be synthesized from commercial diols and triols using esterification and the Regitz diazo transfer reaction (Scheme 1C). The thermal decomposition of the synthesized first and second generations of cross-linker 1G and 2G provides the corresponding bis-carbene that cross-links the linear polymer chains by C−H activation and insertion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, we propose a carbene-mediated polymer cross-linking strategy using compounds that contain two or more carbene precursors. In accordance with this concept, thermal or photochemical conditions were nicely reported to cross-link two polymer chains using bis-diazirine-based cross-linkers; however, tedious synthetic procedures and quantitative loadings (100 wt %) were required for the cross-linkers. A macromolecular cross-linker containing the diazo groups was elegantly reported and applied in the surface modification. , …”
Section: Introductionmentioning
confidence: 99%
“…One approach that circumvents the problem of surface treatment and enables surface attachment with simultaneous crosslinking of the polymer film is based on insertion reactions. [ 8,19–25 ] For this purpose, dormant crosslinker groups are incorporated into the polymer chain during polymerization, which can subsequently be activated by an external stimulus such as thermal, photochemical or mechanical stress, leaving behind a reactive species. [ 8,19,20,22–26 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 8,19–25 ] For this purpose, dormant crosslinker groups are incorporated into the polymer chain during polymerization, which can subsequently be activated by an external stimulus such as thermal, photochemical or mechanical stress, leaving behind a reactive species. [ 8,19,20,22–26 ]…”
Section: Introductionmentioning
confidence: 99%
“…Prucker et al have recently revealed a wide range of UV- and thermally active cross-linkers leading to the network formation via C–H insertion cross-linking (CHiC) reaction mechanism. Accordingly, a precursor copolymer comprising UV-active methacryloyloxybenzophenone (MABP) is deposited on the silicon or a glass substrate precoated with a monolayer of benzophenone-containing silanes . Upon UV irradiation, the benzophenone units present in the polymer and substrate are activated, triggering simultaneous cross-linking and surface-attachment reactions, thus creating surface-attached networks.…”
Section: Introductionmentioning
confidence: 99%